A qualitative study of Internet use comparing the experiences of people with physical disabilities and early onset dementia - Young, Alexandra L. (2020)
People living with Early Onset Dementia and/or physical disabilities face distinct challenges in accessing increasingly digitised services and information. Relatively little is known about how either of these groups access and use the internet on a day-to-day basis, or their plans to negotiate changes in access.